2006
DOI: 10.1007/s10209-006-0029-9
|View full text |Cite
|
Sign up to set email alerts
|

Website design attributes for retrieving health information by older adults: an application of architectural criteria

Abstract: The objectives of this research were to identify design attributes to develop easy-to-use websites for older adults. Forty-one males and 58 females (age range 58-90) were asked to retrieve information on a healthrelated topic from the NHS Direct and Medicdirect websites, and were asked to fill in a website evaluation questionnaire. An exploratory factor analysis of data identified navigation/search usability, link usability, usefulness and colour as important dimensions of a senior-friendly website. A two-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…A study of website design attributes for retrieving health information by older adults found navigation / search usability, link usability, usefulness and colour to be important features. 16 There are no previously published studies looking at the quality of information and readability of websites about AMD. Stone et al 17 performed a similar search in 1998 to assess whether sites featured conventional or unproven treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A study of website design attributes for retrieving health information by older adults found navigation / search usability, link usability, usefulness and colour to be important features. 16 There are no previously published studies looking at the quality of information and readability of websites about AMD. Stone et al 17 performed a similar search in 1998 to assess whether sites featured conventional or unproven treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A poorly designed navigational system, excessive or distractive use of color, small font size, overcrowded pages, and a difficult to use search engine are just a few examples of how poor Website design can reduce ease of use for older adults. Studies have shown that a well-designed Website can partly compensate for differences in older adults' prior experience during an information retrieval task [7,8]. Age can influence use among older adults, and it has been suggested that a ''grey'' digital divide may exist [9].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Nayak, Priest, Hamilton, and White (2006) shows that users become dissatisfied because of the failure to find relevant information and because of the slow access to Websites. Many studies highlight the factors that could contribute to the failure in finding information.…”
Section: Introductionmentioning
confidence: 98%